Foundations of global health & human rights - Gostin, Lawrence O. (Lawrence Ogalthorpe); Meier, Benjamin Mason (New York, NY : Oxford University Press, 2020)
A detailed understanding of the evolving relationship between global health and human rights, bringing together leading academics in the field to explain the norms and principles that define it, examine the methods and tools for implementing human rights to promote health, apply essential human rights to leading public health threats, and analyze rising human rights challenges in a rapidly globalizing world.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 5, 2020).
Keywords: Right to health; World health